Large Meteorite Impacts III 2005
DOI: 10.1130/0-8137-2384-1.443
|View full text |Cite
|
Sign up to set email alerts
|

Starting conditions for hydrothermal systems underneath Martian craters: Hydrocode modeling

Abstract: Mars is the fi rst place to look for any sign of present or past extraterrestrial life. Its surface shows many features indicative of the presence of surface and subsurface water, while impact cratering and volcanism have provided temporary and local surface heat sources throughout Mars' geologic history. In particular, impact-generated hydrothermal systems could have been some of the most favorable sites for the origin of life on Mars.We present preliminary results of hydrocode simulations of impacts on Mars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(116 citation statements)
references
References 48 publications
4
108
1
2
Order By: Relevance
“…There is currently no obvious correlation of the three central pit types with diameter, contrary to previous studies (Barlow and Bradley 1990). Hydrocode models of impacts into soil-ice mixed targets shows that a vapor zone is produced near the center of most transient craters (Pierazzo et al 2005). Sudden release of this vapor could produce the central pit morphology, but why some pits are on the crater floor while others are raised is not currently understood.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…There is currently no obvious correlation of the three central pit types with diameter, contrary to previous studies (Barlow and Bradley 1990). Hydrocode models of impacts into soil-ice mixed targets shows that a vapor zone is produced near the center of most transient craters (Pierazzo et al 2005). Sudden release of this vapor could produce the central pit morphology, but why some pits are on the crater floor while others are raised is not currently understood.…”
Section: Discussioncontrasting
confidence: 46%
“…The lack of central pit craters on volatile-poor bodies such as the Moon and Mercury argues against cometary impacts alone being the primary cause of central pit formation. Recent numerical modeling of impacts into ice-soil mixed targets shows that a region under the center of the transient crater cavity reaches high enough temperatures for ice to vaporize (Pierazzo et al 2005). Both asteroidal and cometary impacts produce this high-temperature region, although the temperatures are higher for cometary impacts due largely to their higher impact velocities.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is suggested that impact-melt rocks and glasses are likely to be much more common on Mars than previously thought. This is supported by the results of numerical simulations and experiments, which suggest that substantial amounts of melt should be produced from impacts into ground-ice-rich targets on Mars (Pierazzo et al 2005;Stewart and Ahrens 2005).…”
Section: Early Observations Using the Mars Global Surveyor Marsmentioning
confidence: 64%
“…Part of the rationale for using a wet porosity is to 298 investigate whether it leads to a significant increase in ejection velocity, as suggested by Kieffer 299 and Simonds, 1980 (Artemieva, 2007). Specific strength properties of porous rocks were not 300 taken into account, however special EOS, assuming a total thermodynamic equilibrium between 301 water and calcite, has been constructed similar to a basalt-water mixture (Pierazzo et al, 2005). 302…”
mentioning
confidence: 99%